2011
DOI: 10.1021/ef201323j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inherent Metals on NO Reduction by Coal Char

Abstract: Five coal chars were prepared in a flat flame flow reactor (FFR) which can simulate the temperature and gas composition of a real pulverized coal combustion environment. Reactivity of these chars with NO in the temperature range of 1273–1573 K has been characterized by experiments in a high-temperature drop tube furnace (DTF). Two normalized parameters (X̅ and m c) are proposed to analyze the effect of inherent metal content on char reactivity. The inherent metal catalysts in chars, such as magnesium, potassiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The pyrolysis and gasification, combustion efficiency, and pollutant emissions of Zhundong coal will be affected as a result of the higher alkali metal content in the coal . The previous research studies by the authors and their team indicated that the heterogeneous reaction of NO is an important component of the NO reduction. The physical and chemical characteristics of coal, such as the specific surface area of char and metal oxide contents, are important factors affecting the reduction of NO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pyrolysis and gasification, combustion efficiency, and pollutant emissions of Zhundong coal will be affected as a result of the higher alkali metal content in the coal . The previous research studies by the authors and their team indicated that the heterogeneous reaction of NO is an important component of the NO reduction. The physical and chemical characteristics of coal, such as the specific surface area of char and metal oxide contents, are important factors affecting the reduction of NO.…”
Section: Introductionmentioning
confidence: 99%
“…The physical and chemical characteristics of coal, such as the specific surface area of char and metal oxide contents, are important factors affecting the reduction of NO. Furthermore, sodium in coal improved the activity of in situ coal char, promoting the heterogeneous reduction of NO by coal char in the boiler, , thereby increasing the reduction rate of nitrogen oxides. However, the micromechanism of the heterogeneous reduction of NO on the sodium-doped char surface is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…There are abundant coal resources in the Zhundong area of Xinjiang, but the content of sodium oxide in Zhundong coal is more than 2%, which belongs to typical high-sodium coal . Sodium in coal not only promoted the pyrolysis and gasification process of coal , but also improved the activity of in situ coal char, thus promoting the heterogeneous reduction of NO by char in the reburning zone of a boiler, and decreased the nitrogen oxide emissions. The effect of sodium additives on the release of fuel nitrogen by using TG/EGA (thermogravimetry/evolved gas analysis) equipment has been studied by Liu et al, and it was found that the presence of sodium catalyzed the reduction of NO by char.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional NH 3 –SCR, carbon/char-SCR owns the advantages of low cost, having little problem with duct deterioration and reductant slip . In general, noble metal containing catalyst has a high activity in NO x -SCR, but the high price of noble metal has driven researchers to develop low-cost transition metal catalysts, such as carbon supported Fe, Co, Ni and Cu. , Active carbon supported Cr and Cu catalysts, , and char supported Fe, Cu and Co catalysts all showed activity in NO x -SCR, in which carbon material functioned as the support and reducing agent. , Note that in some reports, carbon doped/coated catalysts were synthesized, while carbon was only used as the catalyst support and NH 3 as the reducing agent. , Since electroplating sludge contains various metal species and organic matters, its pyrolysis can generate metal/metal oxide/carbon mixture, which would be a potential substitution for metal catalyst in NO x -SCR.…”
Section: Introductionmentioning
confidence: 99%